Analytic epistemology of education a groundwork for rationality as the fundamental aim of education - Cunanan, John Israel U.; Muega, Michael Arthus G.; Acido, Maricris B.; Marquez, Leander P.; Canuto, Abigail Thea O. (Quezon City College of Education, University of the Philippines Diliman, 2022)
The educational aim-discourse has been virtually set aside or assumed to have categorically been settled by educational policy-makers, administrators, teachers, parents, and students. This study aims to ventilate interest in such an important, but decidedly neglected subject matter that has kept many prominent philosophers busy. It is a fact that there is an overabundance of aims of education, but this work attempts to elucidate the idea of fundamental aim of education by arguing that rationally be the fundamental aim of education (or the RFAE thesis). It does so in four ways. First is to propose and argue for a set of ten criteria that shall be used to determine whether something is a tenable fundamental aim of education, viz., (1) it must be a substantial property of human beings (2) it must enable the individual to exercise genuine autonomy, (3) contribute directly toward the attainment of a flourishing life, (4) it must be useful in such a way that it makes possible economic involvement, (5) it must furnish the individual for a life in a democratic society, and toward becoming a good citizens, (6) it must touch on the formation of certain dispositions, (7) it must be a common good, (8) it must possess justificatory power such that it is able to justify accepted educational intuitions, theories, ideas, and objectives, (9) it must be open-ended, and (10) it must be acceptable of providing clear, doable, and economical directions for implementation. Second is to argue for the necessary of the idea of fundamental aim of education. There is scarce to nothing in the available literature on the answers to the first and second; hence, they are the contributions of the study to the existing discourse. Third is to propose a tenable theory rationality (couched in terms of rational person) that is appropriate in education. Lastly is to argue that the proposed account of rationality (couched in terms of rational person) adequately satisfies all the criteria of a fundamental aim of education. Overall, this work in philosophy of education, viz., the RFAE thesis, aims to provide direction and guidance to educational practice from a foundational level. In addition, this study proposes and formulates a philosophical methodology apt for educational research, which is called ‘analytical philosophy of education,’ and having three components: philosophical reconstruction, conceptual analysis, and philosophical justification. This methodology is employed in answering the questions posited above. This study also aims to contribute to the growing field within philosophy of education called epistemology of education.
Thesis
Includes bibliographic references (257- 267 leaves)
Keywords: Education -- Aims and objectives; Education -- Philosophy; Education -- Study and teaching